Orion, Gove County - Zerr, Brad (Kansas State University, The Chapman Center for Rural Studies, 2010)
This study of the slowly-vanishing town of Orion explores the western Kansas environment and the founding of a community in 1886. Wheat farmers claimed large farms in this area. Named for a schoolteacher, Orion had a vital life through World War II, when a gunnery range kept it vitalized. A few buildings, an abandoned store, and a cemetery remain. This study contains on-site photographs and personal research by the author.
Brad Zerr, “Orion, Gove County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/1.
Keywords: Aerial gunnery range; Brad Zerr; Gaeland Cemetery; Gove County; Orion; School